Competências para a tomada de decisão do gestor de saúde em região de fronteira internacional - Loureiro, Nina Rosa Gomes de Oliveira (2022)
Introduction: The concept of competence in health management in a border region is related to the ability to transform theoretical knowledge into skills and attitudes that respond to the needs and demands of the complex work process in the territory. Objective: To analyze the process for decision making in health and the competencies required for managers who work in Primary Health Care in an international border region. Methods: A descriptive and cross-sectional study, with a mixed approach, developed in three stages, with professionals occupying management positions in the municipality of Foz do Iguaçu, Paraná. In the first stage scientific evidence on health decision making competencies was identified through a literature review. In the second stage, the knowledge of managers about health management decision making was measured using a semi-structured questionnaire based on Herbert Symon’s Decision-Making Theory. In the third stage, individual interviews were conducted with each manager, providing the opportunity to assess the necessary competencies and the competency gaps in PHC in an international border region. The answers to the qualitative open questions were submitted to content analysis of the thematic modality type proposed by Bardin. Results: Twenty-three managers participated in the study, with a mean age of 43.6 years, most of them female, with complete college education. Most of the interviewees were trained in the health area and their average length of professional experience was 18.8 months. The speeches of the participants allowed us to establish three analytical categories: weaknesses in decision-making; competencies for assertive decision-making and; expected advances. Conclusions: The approach to public health in the Triple Border area is fragmented and affected by multiple social, economic, cultural and political challenges that are not addressed jointly between the countries. The iguaçuense health system, in the face of its doctrinal principles of universality, equity and integrality embraces an expressive demand of cross-border users not registered in the health teams, thus hindering decision-making.